Effectiveness of Traffic Education in Reducing the Number of Student Traffic Violations in Karawang Police Jurisdiction - Putra, I Gede Putu Surya Wibawa (Police Studies Review, 2024)
Karawang Regency is one of the industrial areas that has high traffic problems such as traffic violations. Students have a high level of traffic violations. This illustrates the lack of awareness and knowledge about traffic among students. The purpose of this research is to describe the profile of Student traffic violations, the implementation of the Traffic Seminar and the Effectiveness of Traffic Education in reducing the number of Student Traffic violations with the location of the study being in the Karawang Police Jurisdiction. This study uses qualitative method, while the theories and concepts used to analyze this problem are Law Enforcement Theory, Management Theory, Communication Theory, Effectiveness Concepts, Traffic Violation Concepts, Kamseltibcar Lantas Concepts and Traffic Education Concepts. Data collection techniques used in this study are interviews, observation, and study of documents. The results obtained in this study are aplication of law by traffic police are still lacking of firm, the targets in the implementation of the Traffic Education at Karawang Police Jurisdiction are still less effective, inadequate facilities and infrastructure as well as the quality of knowledge from the personnel of the service units that are still lacking because they have not implemented the vocational traffic education yet, which causing quite high traffic violations cases , so as not to create Security, Safety, Discipline and Fluency in traffic (Kamseltibcar Lantas).